Regional programme strengthened - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Following on a workshop of its partners held in August 2000, the Southern African Centre for Cooperation in Agricultural Research and Training (SACCAR) has embarked upon a Regional Information Project (RIP). The RIP will be one of the four specific...